Utilización de la tecnología de impresión 3D FDM para crear una lámpara con diseño personalizado (JÓVENES EN LA CIENCIA, 2025)
In this work, the process of creating a custom-designed lamp using Fused Deposition Modeling (FDM) 3D printing technology is presented. The project includes the preparation of a vector illustration, conversion to 3D model, slicing, multicolor printing, and final assembly with LED integration. Free and accessible tools such as Tinkercad and online lithophane generators are used, and various filaments and printer settings are tested to achieve optimal quality. The study demonstrates the effectiveness of FDM for producing functional and aesthetic home decor items in a cost-efficient and creative way.